Habitat management for conservation a handbook of techniques - Ausden, Malcolm; Oxford eBooks (Oxford : Oxford University Press, 2007)
This practical handbook describes the principles and techniques of managing and creating habitats worldwide including grasslands, forests, scrub, freshwater wetlands, coastal habitats, arable land, urban areas and gardens. It is essential reading for conservation biologists.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Habitat conservation; Wildlife habitat improvement; Habitat (Ecology); Electronic books